Drift Capacity Of Lightly Reinforced Soft Storey Structures - Wibowo, Ari (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2013)
Lightly reinforced concrete columns and soft storey configurations are prevalent in many old buildings in regions of lower seismicity. This type of structure is believed to have a very low lateral load and drift capacity from a conventional design perspective. Furthermore, the application of design standards in low and moderate seismic regions such as Australia, results in most of the lightly reinforced structures being deemed unsafe in an earthquake. Therefore, an earthquake damage reconnaissance, experimental field test, and laboratory study of non ductile columns has been undertaken to examine the drift capacity and failure mechanism of such columns. Firstly, a field reconnaissance was conducted in China after the Wenchuan Earthquake in 2008, particularly in regions with similar design intensity MMI VI to VIII experienced in Australia. A comparison between the Wenchuan Earthquake and the characteristics of design earthquakes in Australia was made to provide insight for the development of future design standards and for the assessment of existing buildings in Australia. A unique experimental field testing of a precast soft storey building in Carlton Melbourne was then undertaken. Four tests were conducted to measure the drift capacity and loaddeflection behaviour of such buildings. The experimental results together with a comparison with theoretical predictions showed that the precast columns with weak connection had significant displacement capacity controlled by the column rocking irrespective of strength degradation. Lastly, a laboratory research project has been undertaken to investigate the collapse behaviour of insitu lightly reinforced concrete columns. The effect of variation of axial load ratio and longitudinal reinforcement ratio on flexural, yield penetration, and shear displacement as components of the drift capacity were observed. Interesting outcomes showed that lightly reinforced concrete columns were able to sustain lateral drift considerably greater than the code recommendations, whilst the present shear capacity predictions tended to overestimate the nominal shear strength of the column.Â